ACCOUNTABILITY OF OPERATIONAL ASSISTANCE FUND MANAGEMENT SCHOOL (BOS) AT SMP NEGERI 1 PALLANGGA IN GOWA DISTRICT - Dewi Ashy Shoraya; Muhlis Madani; Fatmawati (INJOSEDU: International Journal of Social and Education, 2025)
Management Accountability and School Operational Assistance (BOS) at SMP Negeri 1 Pallangga in Gowa Regency. Master of Public Administration Study Program, Unismuh Makassar Postgraduate Program. Supervised by Muhlis Madani and Hj. Fatmawati. This study aims to analyze the accountability of the management of school operational assistance funds (BOS) at SMP Negeri 1 Pallangga; and to understand the obstacles found in the management of school operational assistance funds (BOS) at SMP Negeri 1 Pallangga. This research used a descriptive qualitative approach with a case study research type combined with triangulation techniques. The data collection techniques in this research are interview, observation and documentation. The results of this study indicate that the accountability of BOS fund management at SMP Negeri 1 Pallangga has been analyzed using 3 indicators of management measurement, namely: a) The preparation process is through a meeting (all teachers and stakeholders, where the meeting is held once a year. In the meeting, it will be discussed and agreed upon and then compiled in the RKAS (School Budget Activity Plan). BOS funds are calculated based on the number of students, where in 1 year there will be 1 change, namely the distribution mechanism of 3 disbursements of funds in 1 year. b) The purchase of school facilities and infrastructure can be accessed through the SIPlah application, after selecting the items that are prioritized then going to SulSelBar bank to collect the budget and transferring it to the treasurer to use the budget. c) Evaluation and supervision are carried out periodically and continuously, both internally and externally. Meanwhile, the obstacles to the management of BOS funds at SMP Negeri 1 Pallangga were the use of the SIP application, which was still in the adjustment process because it was a new policy program. Sometimes there were still treasurers of each junior high school who were not proficient in using the application and needed to be guided properly. This SIPlah application also has its own obstacles in running the application, namely constrained by a poor internet network, which will interfere with the transaction process. Then, if there is a delay in the disbursement of BOS funds, the SIPlah application cannot be used directly.